Seventy percent of the Mycobacterium tuberculosis isolates in Hong Kong represent the Beijing genotype. - Chan, M. Y. (Cambridge University Press, 2001)
We used spoligotyping to study 500 randomly selected pretreatment Mycobacterium tuberculosis (MTB) strains isolated in Hong Kong during the 2 year period 1998-9. It was found that amongst all MTB strains studied, the 'Beijing' genotype strains were highly prevalent in our geographic area, representing about 70% of the isolates. Unlike previous observations in Vietnam, no significant associations were found either between 'Beijing' genotype strains and all other anti-tuberculosis drug resistance phenotypes, or with particular patients' age groups, except for a weak association with isoniazid susceptibility. Eighteen of these strains exhibited spoligotype patterns that were similar but not identical to the 'Beijing' specific pattern. This is the first geographical area where genetic diversity among 'Beijing' genotype of MTB strains has been observed on this scale.